Climbing Mount Rainier; descriptive of an ascent of the highest peak in the U.S.--exclusive of Alaska--where living glaciers are found - Wheeler, Olin D. (Olin Dunbar), 1852-1925 (W.C. Riley, 1901)
Printed on cover: Riley's Northern Pacific Monographs No. 2. Includes the characteristics of the mountain, history of first ascents and Mount Rainier National Park, camping in the park, the climbing route to the summit and what to expect.